CULTURAL IMAGE CONSTRUCTION IN SHORT VIDEOS: A COMPARATIVE FRAME ANALYSIS OF CONTENT POSTED ON PEOPLE’S DAILY’S TIKTOK ACCOUNT - Yang, Juan; Muhammad Hakimi Tew Abdulla; Yuslinda Mat Yassi; Massila Hamzah (Fonseca, Journal of Communication, 2025)
This study investigates how framing and narrative in People’s Daily’s TikTok short videos shape the Chinese cultural perspective. The research aims to understand the dominant frames, narrative approaches, and connotative features of these videos and their impact on China’s national image. A qualitative approach was adopted, involving 10 media specialist interviews and content analysis of videos posted between October 1, 2021, and 2023. Thematic analysis was used to identify video topics, while comparative frame analysis compared the portrayal of China in these videos. The “culture image” highlights China’s comprehensive strength and global economic participation, including trade, poverty reduction, and the Belt and Road Initiative, presenting China as a major economic force that improves lives and promotes economic cooperation. Chinese economic leadership in stability, prosperity, and international cooperation is highlighted. The study demonstrated how state media strategically shapes China’s global image through narrative and framing, using cultural diplomacy to win over audiences. The findings enhance our understanding of the effects of media narratives on national image and highlight the potential of storytelling in cultural image. The study underscores the importance of framing and narrative in influencing national perceptions in the digital age. It highlights the role of digital platforms in allowing governments to control their global image and public opinion, calling for further research on digital media’s impact on cultural image and audience engagement. The study has significant implications for media and policymakers in enhancing cultural image communication and using narrative and visual communication to convey cultural values and engage viewers.